AN EMPIRICAL STUDY FOR EVALUATING PERFORMANCE OF KING ABDULAZIZ INTERNATIONAL AIRPORT WITH SIX SIGMA - Basahel, Abdullah; Alqarni, Abdullah M. (APTIKOM Publisher, 2019)
This research is intended to evaluate the efficiency of proceures and processes used by the King AbdulazizInternational Airport (KAIA) in Jeddah, Saudi Arabia with the help of Six Sigma. For, we have framed differentobjectives for analyzing the effect of six sigma in decision makings and quality control of the KAIA. The aim is also tofind out the relationship of Six Sigma on an information system used by KAIA. We have used the qualitative researchmethod (semi-structured interview method) with the target population of five employees working at KAIA. Qualitativedata was collected from participants through transcribed, audio-recorded and codes. Thematic analysis was carriedout in order to obtain the study result. Our study finds that there is a significant effect of Six Sigma in streamlining ofall the processes of KAIA, which contributed towards the improvement of the quality and providing better control. Wefound that the KAIA applies KPIs to measure the decision makin, empowering the decision makers or managers. Wehave also reflected on the role of Six Sigma towards the effective performance of individuals in finance, customersupport, and internal business process and team development.